Performance of thin-film BIPV as double sloped pitched roof in buildings of Malaysia - Kumar, Nallapaneni Manoj; Sudhakar, K.; Mahendran, Samykano (Taylor & Francis, 2018)
Solar energy in built environments became more popular in the recent years emerging as building integrated photovoltaics (90° façade and 0° roof BIPV). However, in most cases, residential buildings have varying roof pitches instead of 0° roof. In this context, it is significant to assess the energy output and performance of double-sloped pitched roof thin-film BIPV at different angles and orientation. Results show that the performance of the BIPV inclined at 15° and east orientation is better among the other orientation and angles.